2022
DOI: 10.1186/s12909-022-03912-8
|View full text |Cite
|
Sign up to set email alerts
|

The perceived value and impact of virtual simulation-based education on students’ learning: a mixed methods study

Abstract: Background Virtual simulations are used throughout healthcare training programs to enable development of clinical skills, however the potential for virtual simulation to enhance cognitive and affective skills is less well understood. This study explored pre-clinical optometry students’ perceptions of the impact of virtual simulation on the development of core competency skills including patient-centred care, communication, scientific literacy, and evidence-based practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Virtual simulation can develop students’ perception of their professional identity [ 14 ]. Researchers found that student participants reflected that the VSIP were a way to interact with people from different cultures and professional environments to begin to establish cross cultural communication skills and interconnection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual simulation can develop students’ perception of their professional identity [ 14 ]. Researchers found that student participants reflected that the VSIP were a way to interact with people from different cultures and professional environments to begin to establish cross cultural communication skills and interconnection.…”
Section: Resultsmentioning
confidence: 99%
“…Virtual simulation motivates optometry students to learn when they see relevance to their future roles and experience authentic learning activities. A previous study on optometry students’ perceptions of virtual simulation found that the correct level of realism generates enough immersion to feel as though they were performing work related training [ 14 ]. In this study participants referenced the meaningfulness of the VSIP in the IEC was supported by the authenticity in the learning experience, “We learn optometry in a real way… rather than learning it theoretically…” (P37).…”
Section: Discussionmentioning
confidence: 99%
“…Although mirror training with Mirrosistant has a positive impact on students’ perceptions of direction and distance, the simple mirror training device could not replace virtual simulation dental training system, such as Voxel-Man simulator (Voxel-Man, Hamburg, Germany) [ 20 ], Kobra Simulator (Haptikfabriken AB, Stockholm, Sweden) [ 21 ], and SIMODONT [ 22 ]. Presently, virtual reality simulators are becoming an essential part of modern education [ 23 , 24 ]. In pre-clinical settings, virtual reality applied in dentistry constantly serves as a method or an adjunct to improve fine motor skills and hand–eye coordination [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intention is to allow learners to participate in active learning through deliberate practice and reflection [ 15 ]. Like other forms of simulation, VS can also allow learners to assume different perspectives [ 16 ]. However, technology itself does not always deliver on its promises—education must be designed to make it more inclusive [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are emerging empirical and conceptual examples of how VS in HPE could influence attitudes toward inclusion in the future healthcare workforce [ 16 , 19 , 20 ]. One empirical study proposes a reflective tool to support simulation delivery teams to evaluate personal assumptions and bias within a VS experience [ 21 ].…”
Section: Introductionmentioning
confidence: 99%